Patterns of treatment and outcomes of patients with metastatic HER2-low breast cancer treated with CDK4/6 inhibitors and hormone therapy - Federico Sottotetti; Barbara Tagliaferri; Gianpiero Rizzo; Raffaella Palumbo; Giulia Chessa; Chiara Raso; Lorenzo Perrone; Alberto Malovini; Valentina Tibollo; Laura Deborah Locati; Paolo Pedrazzoli; Angioletta Lasagna (Drugs in Context)
Background: The 2018 American Society of Clinical Oncology/College of American Pathologists guidelines classified immunohistochemistry (IHC) 1+ or 2+, FISH-negative breast cancer as HER2-low. To date, only a few studies have investigated the role of HER2-low status in patients with hormone receptor positive/HER2– (HR+/HER2–) metastatic breast cancer (MBC) during CDK4/6 inhibitor (CDK4/6i) therapy.